Konsep Emansipasi Intelektual Menurut Jacques Ranciere dan Relevansinya Terhadap Pendidikan di Indonesia - Dewa Gede Putra Atmajaya; Oktovianus Kosat; Mario Venerial Umbu Zerri (Dinasti Review Publisher, 2024)
Education is one of the most important aspects that requires serious attention in a country. Education is the heart and capital that can brighten the future of a nation. So every country continues to update and evaluate its education system based on existing realities. There is always an overhaul or update to adjust the system so that education can run effectively. Indonesia is also making changes to its education system. However, do these changes ensure justice and equality for learners? Are learners really the subject of the existing education system? So the purpose of this research is to examine the existence of practices in the world of education that produce inequality. The main theory used is Jacques Ranciere's concept of intellectual emancipation. The method used is literature. It was found that inequality often occurs in the world of education through the system implemented. The results of this study can provide a new understanding of the importance of a country prioritizing equality in an education system.